EMG signal processing by wavelet transformation - applicability to alpine skiing - Kröll, J.; Wakeling, J. M.; Seifert, J.; Müller, E. (Science and Skiing IV, 2009)
INTRODUCTION: To now it has been primarily amplitude and timing information that is extracted from electromyography (EMG) in alpine skiing. However, the EMG frequency also contains information about the pattern of activation of different muscle fiber types (fast/slow twitch). This additional information can help to describe the muscle recruitment in a more in-depth manner. The analysis of the frequency content was performed previously in alpine skiing by calculating the median power frequency (Kroll 2005). This method, however, resulted in the loss of timing information, which is essential in alpine skiing research. The aim of the current project was to perform a time-frequency analysis of the EMG intensities during alpine skiing using wavelet transformation. Our primarily interests were to determine functional differences in recruitment and timing within the quadriceps muscle and the influence of geographic variations over a group of skiers.